Analysis of blood pressure and selected cardiovascular risk factors in the Democratic Republic of the Congo: the May Measurement Month 2018 results. (28th August 2020) - Buila, Nathan B; Ngoyi, Georges N; Bayauli, Pascal M; Katamba, Fortunat K; Lubenga, Yves N; Kazadi, Serge M; Kiadi, Glodie D; Lepira, François B; Kabanda, Gilbert K; Kika, Mireille L; Beaney, Thomas; Ster, Anca Chis; et al.
Abstract: Hypertension (HT) is the largest contributor to cardiovascular disease mortality and is characterized by high prevalence and low awareness, treatment, and control rates in sub-Saharan Africa. May Measurement Month (MMM) is an international campaign intended to increase awareness of high blood pressure (BP) among the population and advocate for its importance to the health authorities. This study aimed to increase awareness of raised BP in a country where its nationwide prevalence is yet unestablished. Investigators trained and tested how to use the campaign materials, collected participants' demographic data, lifestyle habits, and obtained from each one three BP measurements. Hypertension was defined as a BP ≥140/90 mmHg, or use of antihypertensive medication. Of the 18 719 screened (mean age 41 years; 61.4% men), 26.1% were found to be hypertensive of whom 46.3% were aware of their condition and 29.6% were taking antihypertensive medication. The control rate of HT was 43.0% in those on medication and 12.7% among all hypertensive respondents. Comorbidities found were—diabetes (3.3%), overweight/obesity (35.5%); and a previous stroke and a previous myocardial infarction were reported by 1.2% and 2.0%, respectively. Imputed age- and sex-standardized BP was higher in treated hypertensive individuals (135/85 mmHg) than those not treated (124/78 mmHg). Based on linear regression models adjusted for age and sex (and an interaction) and antihypertensive medication, stroke survivors, those who drank once or more per week (vs. never/rarely), and overweight/obese participants were associated with higher BP. MMM18 results in the Democratic Republic of the Congo corroborated the high prevalence of HT in Kinshasa screenees with low rates of treatment and control. Extension of the MMM campaign to other parts of the country is advisable.